Modern Methods of Controlling Wound Healing after Fistulizing Glaucoma Surgery. Risk Factors and Antimetabolites - S. Yu. Petrov (Oftalʹmologiâ)
The article describes modern approaches to controlling wound healing after fistulizing glaucoma surgery. It provides a classification of refractory glaucoma degrees and summarizes risk factors for excessive scarring. Author describes various applications of widely administered in clinical practice antimetabolites (5 fluorouracil, mitomycin C) in patients with different degrees of excessive wound healing risk. The review also recounts international experience of steroidal and nonsteroidal anti-inflammatory drug use and their efficacy research study results. Much attention is given to new strategies of wound healing regulation after fistulizing glaucoma surgery, aimed at enhancing its results. The article describes characteristics and modes of action of medicinal agents effecting the cytoskeleton, such as Rho-kinase inhibitors and taxane anticancer agents. A detailed account of modes of effecting wound healing through regulating the process growth factors, proteinases and cytokines is also given. Possible strategies include antifibrotic cytokine interferon-α application and inhibiting the following agents: transforming growth factor β; connective tissue growth factor (CTGF), that controls extracellular matrix components production and cicatrical tissue formation; vascular endothelial growth factor (VEGF), that indirectly influences fibrotic activity through its angiogenic effect and also has a supposed direct effect on fibroblast activity; proinflammatory placental growth factor (PIGF), that increases bleb area size and its survival time, and decreases postoperative angiogenesis, inflammation and fibrosis intensity. The last part of the article gives a brief report on less widespread and researched methods of wound healing regulation, such as suppressing the activity of matrix metalloproteinases and amniotic membrane application.